Short Dance Film: Construction of the Arts and Design Project Subject during COVID-19 Pandemic - Supiarza, Hery; Sabaria, Ria (Bina Nusantara University, 2022)
The research discussed short dance films as the product of the Arts and Design Project subject at FPSD Universitas Pendidikan Indonesia during the COVID-19 pandemic. The importance of a collaborative learning model between two disciplines, dance and film, had emerged the notion of creating an art product. The research aimed to create dance film products as a form of student constructive idea. With the participatory action research method, the data were collected and validated to be analyzed and then embodied in the form of a dance film product. The research was applied to 53 students in collaboration between the Department of Dance Education and the Film and Television Study Program, divided into eight small groups of six to seven members. The action stages of the research were: (1) observation and analysis; (2) collection of ideas and notions in the form of a script; (3) testing; (4) shooting; (5) product. The research finds that: (1) through a collaborative learning model, the subject of Arts and Design Project could be implemented to create a dance film product, short dance film; and (2) during the COVID-19 pandemic, collaborative learning could enable students to keep productive to create the product of their learning result. As an advantage, the research result can be used as a learning sample of production-based subjects during the pandemic where the learning and teaching activity should be done at home.Â